Metacognitive awareness of reading strategies among EFL high school students in China / Li Yang - Li, Yang (2016)
Readers’ metacognitive awareness of reading strategies has always been the interest of L2 reading research (Zhang, 2001). This study reported an investigation of 118 Chinese EFL students’ metacognitive awareness of reading strategies and the relationship between metacognitive awareness and actual reading performance. Data was collected through the Survey of Reading Strategies (SORS) and one internal reading exam. The findings showed that students’ overall metacognitive awareness of reading strategies was at a moderate level with the highest level on problem-solving strategies, followed by global strategies and support strategies. Students from high English proficiency group reported considerably higher metacognitive awareness in global and problem-solving strategies compared with the students from intermediate and low proficiency groups, which provided the evidence that readers’ metacognitive awareness of reading strategies was related to their English language proficiency. Further investigation revealed that the metacognitive awareness of reading strategies as measured by SORS was positively associated with students’ actual reading performance, accounting for 23% of the variance in English reading performance. Analysis of individual factors showed that global strategy was a significant predictor of reading performance. The findings of this study also showed a possible way for English reading instructors to assess readers’ metacognitive awareness of reading strategies, so that they can better interpret readers’ learning needs and design suitable strategy-based reading curriculum.”